In vitro evaluation of antioxidant, antiproliferative potentials of bioactive extract-cum-rutin compound Isolated from Memecylon edule leaves and its molecular docking study. Issue 1 (2nd January 2016) - Srinivasan, R.; Natarajan, D.; Shivakumar, M.S.
Abstract: The current study was planned to investigate the antioxidant and anti-proliferative potential of leaf crude extracts and isolated compound (rutin) from Memecylon edule by performing the standard antioxidant and MTT assays. Results suggested that different solvents crude leaf extracts of M. edule expressed varying degree of antioxidant potential on all tested methods (DPPH, NO, OH, O2 - radicals) based on dose depended manner and they also had good reducing ability. Significant high antiradical potential was found in ethyl acetate extract (DPPH IC50 value 26.77 μg/ml, NO IC50 value 27.04 μg/ml, OH IC50 value 30.94 μg/ml, O2 - IC50 value 50.75 μg/ml and FRAP EC50 value 40.43 μg/ml) followed by other extracts. The anti-proliferative activity of potential extract (ethyl acetate extract) which possess high antioxidant activity, and isolated rutin compound was tested (by MTT assay) against U-937 and HT-60 cell lines and the results show dose dependent activity. In addition, docking studies of reported rutin compound exhibits strong inhibition on the active site of VEGFR2 than the co-crystallized ligand N, 2-dimethyl-6-(7-(2-morpholinoethoxy) Quinolin-4-yloxy)benzofuran-3-carboxamide.